1995
DOI: 10.1029/95ja01505
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate occurrence of the electric field fluctuations in the nighttime midlatitude ionosphere

Abstract: The DE 2 satellite observed electric field fluctuations on the topside of the nighttime midlatitude ionosphere. They extended several hundred kilometers in the latitudinal direction with wavelengths of several tens of kilometers, and their amplitudes were a few millivolts per meter. Such fluctuations were often observed at magnetically conjugate points in the northern and southern hemispheres. These electric field fluctuations are perpendicular to the geomagnetic field. They are not accompanied by any signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
125
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(139 citation statements)
references
References 20 publications
14
125
0
Order By: Relevance
“…This difference may be due to the fact that Erlandson and Anderson (1996) used E-field measurements for the Pc1 event detection, while we use B-field fluctuations. Moreover, the local time variation of the DE-2 orbit was locked with the seasonal variation (Saito et al, 1995), which may further contribute to the slight disagreement between our Fig. 4 and Erlandson and Anderson (1996).…”
Section: Temporal Variation Of Event Ratesmentioning
confidence: 64%
See 2 more Smart Citations
“…This difference may be due to the fact that Erlandson and Anderson (1996) used E-field measurements for the Pc1 event detection, while we use B-field fluctuations. Moreover, the local time variation of the DE-2 orbit was locked with the seasonal variation (Saito et al, 1995), which may further contribute to the slight disagreement between our Fig. 4 and Erlandson and Anderson (1996).…”
Section: Temporal Variation Of Event Ratesmentioning
confidence: 64%
“…One may argue that these two conditions lead to lower Alfvén velocity, which can be expressed by the ratio of E-field over B-field fluctuations (e.g. Saito et al, 1995). However, this interpretation should lead to a larger number of Pc1 events in the SAA than in the northern conjugate region: B-field is weaker (due to the SAA) and plasma density in local summer is higher (Lee et al, 2011, Fig.…”
Section: Spatial Distribution Of Occurrence Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The single-band structure with its movement towards the northwest in the Southern Hemisphere (as shown in Otsuka et al, 2004 andShiokawa et al, 2005) make it distinct from the ESF and BW patterns seen frequently on other nights. The only global study of MLI occurrence patterns was conducted by Saito et al (1995) using the electric field and plasma density instruments on the Dynamics Explorer (DE) spacecraft. In the American longitude sector, they showed that Arecibo's location was close to the peak occurrence zone in their statistical summary, while that zone in the Southern Hemisphere was somewhat poleward of El Leoncito's location.…”
Section: Airglow Structures Associated With Mid-latitude Instabilitiesmentioning
confidence: 99%
“…MSTIDs are regionally confined nighttime dynamic plasma density irregularities in the ionospheric E -and F -layers associated with electric field fluctuations that map to both conjugate hemispheres and thus produce significant IHFACs (Shiokawa et al 2003). They have first been found by Saito et al (1995) in electric measurements taken by the DE-2 satellite, and by Park et al (2009) in magnetic field observations taken by the CHAMP satellite. Using data from the Swarm constellation, confirmed that their spatial structure is similar to those of the associated plasma density fluctuations.…”
Section: This Issue)mentioning
confidence: 99%